Test of the modified dual pathway model of eating disorders in individuals with type 1 diabetes. Issue 6 (25th February 2019) - Rancourt, Diana; Foster, Nicole; Bollepalli, Sureka; Fitterman‐Harris, Hannah F.; Powers, Margaret A.; Clements, Mark; Smith, Laura B.
Abstract: Objective: Adolescents and young adults with type 1 diabetes (T1D) demonstrate high rates of disordered eating behaviors (DEBs) and may experience physiological and psychological vulnerabilities not currently included in established risk models of DEBs. This study examined associations among constructs included in the recently proposed T1D‐specific modified dual pathway model and examined age as a moderator of these associations. Method: Participants included adolescents ( n  = 307; age M  = 15.71, SD  = 1.33), young adults ( n  = 313; age M  = 21.20, SD  = 2.10), and adults ( n  = 198; age M  = 30.51, SD  = 2.81) recruited via the T1D Exchange Clinic Registry. Data were collected from participants' medical records and from self‐report questionnaires assessing dietary regimen, dietary restraint, body dissatisfaction, hunger/satiety, diabetes‐specific negative affect, and DEBs. Multiple group path modeling was used to test hypotheses. Results: Approximately 31% of participants were at risk for an eating disorder. The original modified dual pathway model had poor model fit. The addition of three empirically defensible paths improved model fit. Diabetes‐specific dietary regimen, diabetes‐specific negative affect, and hunger/satiety disruption all were associated with DEBs. A fully varying multiple group model by age fit best; however, only the dietary restraint to DEBs pathway demonstrated a distinct pattern across age cohort, which attenuated from the adolescent to the adult cohort. Discussion: This study provides preliminary support for associations proposed in the modified dual pathway model and suggests potential for intervening on disease‐specific risk factors of DEBs in a T1D population.